The profile of the entrepreneur. Cultural construction of post-Fordist labor subjectivity - Rodríguez López, Roberto; Borges Gómez, Efrén (Cuadernos de Relaciones Laborales, 2018)
The rise of entrepreneurship in recent decades is a constant in many economic, political and socio-cultural areas. It tends to present itself as a successful business model, but we want to reveal its imposing aspirations as an undeniable normative reference for the current models of labor subjectivity. The objective of our study is to determine the basic normative traits of the entrepreneur. In order to do this we have analyzed the discourse of self-help literature oriented to the formation of “entrepreneurial subjectivities”. Today, this literature is a privileged space for the production of self-directed personalities in a deeply psychologized contemporary cultural environment. We finally detected seven distinctive features of the entrepreneur, which refer us to an expected model of economic success, but also, to a model that depoliticizes and makes invisible the great precarious working conditions in the new post-Fordist reality.